SIGNIFIKANSI KURATORIAL DALAM PROSES EDUKASI APRESIASIPUBLIK PADA PAMERAN SAPUAN KUAS DAN KELALIMAN BENTUK - Athian, Muhammad Rahman (Universitas Negeri Semarang, 2024)
This paper discusses the concept, purpose and function of art education in the context of national education, with an emphasis on art appreciation. From a cultural perspective, art education is believed to contribute to the formation of creative capacity and cultural awareness of society. The aim of this research is to analyze the curatorial significance of the temporary exhibition